Lumbar disc herniation: review of minimally invasive surgical approaches (Research, Society and Development, 2025)
A herniated lumbar disc is a common condition that can cause intense pain and limit mobility of patients. Surgical treatment becomes a fundamental option when approaching conservative failed. In recent years, minimally invasive (MI) surgical techniques have emerged as promising alternatives to traditional open surgery, offering advantages such as shorter recovery time, reduced post-operative pain and lower rates of complications. The objective of this article is to carry out a review of the minimally invasive surgical approaches for the treatment of lumbar disc herniation, comparing the effectiveness, recovery time and complications associated with these techniques. The review analyzes the effectiveness of these techniques in comparison with traditional open discectomy, focusing on clinical results, recovery time and complications. Also discussed, recent technological advances have been discussed, such as the use of computerized navigation and endoscopy, which emphasize the precision and safety of these procedures. A critical analysis of two reviewed studies reveals that minimally invasive approaches present promising results, but also present limitations, such as the need for greater surgical expertise and the lack of consensus regarding the selection of the ideal method for different types of hernia. The article concluded that, despite the obvious advantages, more studies are necessary to consolidate the indications and optimize the treatment protocols to guarantee better results in the long term.